Konsep Nusyuz dalam Prespektif Gender - Muslim Muslim; Akbar Maulana; Nuur Wahidah; Nur Fitriah (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
The concept of nusyuz in Islam refers to the behavior of a disobedient or disobedient wife or husband in the context of a marital relationship. Traditionally, nusyuz is often identified as a wife's disobedience to her husband, such as disobeying the husband's legitimate orders, leaving home without the husband's permission, or refusing to have sex without a justified reason. However, in some views, nusyuz can also be applied to husbands who do similar things, such as not providing for themselves or treating their wives unfairly